Efficacy of first-line, WHO recommended generic HAART regimens in Indian children - Parakh, A; Dubey, AP; Kumar, A; Maheshwari, A; Saxena, R (Kathmandu University Medical Journal, 2010)
Background: The clinical efficacy of highly active antiretroviral therapy (HAART) in children has been well documented in the developed countries, although most of the regimens are Protease Inhibitor (PI) based which are too expensive. To circumvent this problem World Health Organization (WHO) has recommended Non- Nucleotide Reverse Transcriptase Inhibitor (NNRTI) based regimen for resource-limited countries. Aim: To assess the long-term efficacy of first line World Health Organization (WHO)-recommended generic highly active antiretroviral therapy (HAART) regimens in treatment -naïve children. Materials and methods: Observational retrospective analysis was done. Thirty patients on HAART for > 6 months were included (27 on Stavudine; three on Zidovudine with Lamivudine/ Nevirapine). No protease inhibitors were used. Results: median age was seven years (Interquartile [IQR]: 5.62-8.50) and median duration on HAART was 18 months (IQR: 6-24). No new staging events were observed after six months of initiation of HAART. The median CD4% increased from 6.0 % at baseline to 15.5% at six months, 21.7% at 12 months, 25.4% at 18 months, 24.6 % at 24 months 25.3% at 30 months and 23.7% at 36 months. There was only one case of immunological failure. Stratified analysis based on baseline CD4 % show that even patients with a baseline CD4 % of <5% achieved percentage of >25% at 18-24 months and maintained it subsequently. Significant increase in the weight and body mass index Z scores was observed but significant fall in the height Z scores were observed. This sub group of patients with poor linear height velocity would require detailed endocrine evaluation after testing for viral loads. Conclusions: Non- Nucleotide Reverse Transcriptase Inhibitor based HAART regimens are feasible and effective in long term in resource-limited setting despite initiation of treatment in advanced stages. These can be continued in NACO/WHO scale up programmes at present for children. Key words: HAART in children; India; NNRTI based HAART; resource limited settings; WHO prequalified Antiretroviral therapy DOI: 10.3126/kumj.v7i3.2727 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 220-225